2016
DOI: 10.18632/oncotarget.9870
|View full text |Cite
|
Sign up to set email alerts
|

HER2 reduces breast cancer radiosensitivity by activating focal adhesion kinase in vitro and in vivo

Abstract: Growing evidence has demonstrated that human epidermal growth factor receptor 2 (HER2) is involved in the radiation response to breast cancer. However, the underlying mechanism remains elusive. Therefore, we investigated if HER2 overexpression is associated with radiosensitivity of breast cancer. We constructed breast cancer cell lines differing in HER2 expression by transducing HER2 cDNA or short hairpin RNA against HER2. We then assessed the radiosensitivity and investigated the potential mechanism by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Lysate was purified by centrifugation for 10 min at 4°C and 20–50 μg of solubilized proteins were resolved on 10% or 12% SDS-PAGE [56]. …”
Section: Methodsmentioning
confidence: 99%
“…Lysate was purified by centrifugation for 10 min at 4°C and 20–50 μg of solubilized proteins were resolved on 10% or 12% SDS-PAGE [56]. …”
Section: Methodsmentioning
confidence: 99%
“…5A and B). Our previous study demonstrated that Fak-associated genes were important in HER2-mediated radio-resistance (13). Therefore, the expression of Fak was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Migration assays. The migration assay was performed as previously described (13,14). Briefly, a total of 2x10 4 of MDA-MB-231 or ZR-75-30 were placed in the upper chamber of a Transwell chamber (BD Biosciences) with an 8-µm pore filter between the chambers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo experiences confirmed that HER2 silenced BC cell lines had increased RSI, and that HER2 xenograft tumors had enhanced radioresistance if compared to corresponding controls. These effects on RSI seemed to be related to HER2 mediated up-regulation of phosphorylation of focal adhesion kinase (FAK); as a counterproof, RSI was restored using a FAK inhibitor (11).…”
mentioning
confidence: 99%